Translating Time: Cinema, the Fantastic, and Temporal Critique. - Tompkins, Cynthia (Imagofagia, 2021)
Sobre Bliss Cua Lim. Translating Time: Cinema, the Fantastic, and Temporal Critique. Dirham, Duke University Press, 2009. Palabras clave: reseña, Bliss Cua Lim, Translating Time: Cinema, the Fantastic, and Temporal Critique